Environmental degradation due to tobacco cultivation in Bangladesh: a case study of Doulathpur, Kushtia - Kutub, Md. Juel Rana; Falgunee, Nishat (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Tobacco plant is diseases prone and requires much chemical fertilizers, pesticides and enormous care. Yet, since the liberation tobacco cultivation has become an important part of agriculture in Bangladesh thanks to its promotion by the British American Tobacco Company. Kushtia is one of the major tobacco growing areas of Bangladesh. This paper aims to find out the negative environmental impacts of tobacco cultivation and how environmental degradation causes reduction of soil fertility and increase water pollution, biodiversity damages and deforestation in Kushtia. Research findings revealed that tobacco cultivation had indeed incurred widespread negative impacts on agro-biodiversity, water and soil quality, biodiversity and traditional agro-practices in the study area. Soil and water in the study area were found to be contaminated with toxic pesticides and chemical components that reduced the soil fertility and increased water pollution. The pH levels of both soil and water was found to be less than the minimum acceptable level. Soil was more acidic and water had less dissolved oxygen that indicated severe pollution. Flora and fauna species in the study area were also adversely impacted by the excessive use of agrochemicals in tobacco cultivation. As the drive for profit converted more arable land to tobacco cultivation environmental degradation was enhanced in the study area.